Marx’s and Engels’ attitude towards the national question - Mandić, Stefan (Sociološki pregled, 2022)
The main aim of this paper is to determine how Karl Marx and Friedrich Engels treated the national question. Proclaiming the class as the main historical player, Marx and Engels used to pass easily over the importance of a nation’s player potential. However, practical-political reasons forced them to deal with topics related to the nation. First of all, they were aware of the explosive power of nationalism and because it could significantly influence the initiation of social revolution, but also its inhibition. Due to this fact, it was important for them to make the most of their political activities, but also to control the strength of the national feeling of different peoples. One could say that Marx’s and Engels’s attitude towards the nation was instrumental, i.e. it was seen as a potential tool in the revolutionary struggle. Marx and Engels described the peoples they perceived as the bearers of social revolution as a positive and progressive social force. On the other hand, Marx and Engels treated peoples who had a “reactionary historical role” with contempt and denied their right to exist.
Keywords: Marx; Engels; Marxism; national question; nation